The Influence of Game-Based Learning Models on Reading Literacy Skills of Fourth Grade Students at SDN 24 North Rabangodu, Bima City - Adriani, Asti; Cahyadi, Anggih Tri; Fatimah, Nunung (Journal of Educational Sciences, 2025)
This study aims to analyze the effect of a game-based learning model on the reading literacy skills of fourth-grade students at SDN 24 Rabangodu Utara, Bima City. The research was motivated by the low reading literacy levels of students, as indicated by poor text comprehension, slow reading speed, and limited vocabulary mastery. A pre-experimental method with a one-group pretest-posttest design was employed. The subjects were 18 students who took reading literacy tests before and after the implementation of a snakes and ladders game-based learning medium. Data were collected through tests, observation, and documentation, then analyzed using the Shapiro-Wilk normality test and paired sample t-test. The results showed a significant improvement in reading literacy scores, from an average of 63.56 in the pretest to 81.33 in the posttest (p < 0.05). Game-based learning proved effective in enhancing students’ participation, motivation, and reading comprehension. This strategy is recommended as an alternative for literacy learning in primary schools and can be developed for other literacy aspects through digital media integration.